Etherology, and the phreno-philosophy of mesmerism and magic eloquence : including a new philosophy of sleep and of consciousness : with a review of the pretensions of phreno-magnetism, electro-biology, &c. / by J. Stanley Grimes. - Grimes, J. Stanley (James Stanley), 1807-1903. (Tufts University. Tisch Library., 2015)
[Second edition] /revised and edited by W.G. Le Duc.; 1 online resource (251, 121 pages) : illustrations.; "Introduction to the second edition" (signed W.G. Le Duc): p. 11-16.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.